Sleep-related erectile dysfunction - Gadzalski, Krzysztof; Lorek, Julia; Perski, Karol; Grzywna, Wojciech; Chrabąszcz, Joanna; Baltyzar, Konstancja Anna; Kurek, Maria Michalina; Polit-Różycka, Oliwia Kinga; Zarzycka, Marta (Quality in Sport, 2026)
Introduction: Sleep is crucial for preserving general health, and the emergence of numerous chronic illnesses is associated with sleep deprivation. Recent studies suggest that short sleep duration may also have negative effects on the reproductive system. Sleep disturbances are increasingly associated with erectile dysfunction through their impact on hormonal balance and physiological regulation. Aim of the study: This article summarizes the interplay between physiological processes such as sleep and erection, based on an analysis of information regarding the functioning of the autonomic nervous system, hormones, neurotransmitters, and pro-inflammatory cytokines, as well as the NOS-NO-cGMP signaling pathway and REM-related erections. Material and Methods: A literature review was conducted using PubMed and Google Scholar to identify studies on the physiology of erections and the impact of sleep disorders on the erectile mechanism. Peer-reviewed clinical trials, systematic reviews, and other studies were analyzed to provide a comprehensive overview of the current state of knowledge. Conclusion: Erectile dysfunction is becoming increasingly common, affecting not only older men but also younger men as well. One important contributing factor is poor sleep, which can lead to serious hormonal and neurological disturbances. This disrupts both the molecular mechanism and the functioning of the central nervous system in relation to the development of an erection.